Facile Controlling of the Physical Properties of Zinc Oxide and Its Application to Enhanced Photocatalysis - Tuan Vu Anh; Thi Anh Tuyet Pham; Van Hung Mac; Thanh Hung Nguyen (Journal of Analytical Methods in Chemistry)
In this study, the physical properties of ZnO were facile controlled by the synthesis method with the addition of capping and precipitation agents. As-prepared ZnO samples had different morphologies such as carnation flower-like ZnO (CF-ZnO), rose-flower-like ZnO (RF-ZnO), rod-like ZnO (R-ZnO), and nanoparticle ZnO (N-ZnO) and were characterized by SEM, XRD, N2 adsorption/desorption isotherms, FT-IR, and DR/UV-vis. All samples had a crystallite structure of hexagonal wurtzite type. The CF-ZnO and RF-ZnO samples had the hierarchical structure like a carnation flower and a beautiful rose, respectively. R-ZnO was composed of many hexagonal rods and few spherical particles, while N-ZnO microstructures were made up of nanoparticles with approximately 20–30 nm, exhibiting the largest surface area, pore volume, and pore width among as-prepared samples, and their crystal size and bandgap energy were 17.8 nm and 3.207 eV, respectively. The catalytic performances of ZnO samples were evaluated by degradation of Tartrazine (TA) and Caffeine (CAF) under low UV irradiation (15 W). N-ZnO showed a high photocatalytic activity compared to other samples. Besides, the reaction kinetics was investigated by the first-order kinetic model, and the catalytic performance of ZnO was evaluated through several organic pollutants.